Alteration conditions on the CM and CV parent bodies – Insights from hydrothermal experiments with the CO chondrite Kainsaz. (1st February 2022) - Suttle, M.D.; King, A.J.; Ramkissoon, N.K.; Bonato, E.; Franchi, I.A.; Malley, J.; Schofield, P.F.; Najorka, J.; Salge, T.; Russell, S.S.
Abstract: This study simulates the hydrothermal conditions that existed on carbonaceous chondrite planetesimals in the early solar system. Our experiments are relevant to alteration conditions that existed on the CV parent body and the late stage oxidizing alteration of the CM chondrites. We conducted 11 alteration experiments using chips of the CO3 chondrite Kainsaz. Water was added to each chip and sealed in separate Teflon reaction vessels for 175 days. Samples were altered at different initial water-to-rock ratios (W/R: 0.2–0.8) and temperatures (50 °C and 150 °C). Isotopically doped 17 O-rich heavy water (δ 17 O: +64.5‰) was used in five runs. All samples experienced pronounced alteration under a partially open system environment where gases were able to escape the reaction vessels. The style of alteration (Fe-alkali metasomatism) is similar in all cases. The principal alteration minerals formed are Fe-oxyhydroxides (goethite) and Fe-oxides (magnetite), with smaller quantities of Fe-sulphides. Minor phases formed include fayalite, sulphates (gypsum and Fe-sulphate) and calcite. Nanophase, poorly crystalline phyllosilicates formed in the high-temperature samples but are absent from the low-temperature experiments. In all instances, Mg-rich chondrule silicates remained chemically unaltered although some grains suffered hydrothermal fracture. Chondrule mesostases remained largely unaffected. By contrast, kamacite readily dissolved, acting as a source of Fe and Ni for the fluid phase. A new generation of nanophase Fe-sulphides formed within the matrix, while pre-existing pyrrhotite group sulphides experienced Ni enrichment (<3 at%). In the high temperature samples these sulphides were also partially oxidized, lowering their (Fe + Ni)/S ratio. High-Ni sulphides (pyrrhotite with Ni > 10 at%) were formed in the 150 °C samples, most likely by sulphidation of taenite. Matrix alteration cemented grains together, reducing porosity. The fine-grained matrix shows highly variable degrees of alteration, with minimally altered matrix in direct contact with regions of heavily altered matrix. Chondrule fine-grained rims (FGRs) were preferentially altered. These textures imply that the unaltered matrix readily reacted with the fluid phase, resulting in an efficient depletion of dissolved ions (Fe 2+ and S 2- ), limiting reactivity until further primary phases were dissolved. At larger length-scales the distribution of heavily altered matrix reveals the presence of large ∼100 µm wide channels that meander through the specimens. Their textures resemble features seen in some CM chondrites and the ungrouped CO-like chondrite MIL 07687. We suggest that alteration fronts developed by sustained rapid reaction of matrix with dissolved cations in solution. Our observations provide a mechanism for the establishment and maintenance of geochemical microenvironments on chondritic asteroids. The effects of open system loss notwithstanding, our experiments demonstrate that more advanced alteration is correlated with higher initial W/R ratios. The use of 17 O-rich doped water allowed the isotopic effects of aqueous alteration to be observed. Bulk rock compositions evolved towards the initial water composition, reflecting the incorporation of heavy O into hydrated minerals. Additionally, altered samples shifted in δ 18 O space, reflecting the competing effects of water–mineral fractionation and mass fractionation due to the preferential escape of isotopically light water.